Persistent dyslipidemia in statin-treated patients: Russian real-world clinical practice data (Russian part of the DYSIS Study) - R. G. Oganov; V. V. Kukharchuk; G. P. Arutyunov; A. S. Galyavich; V. S. Gurevich; D. V. Duplyakov; Yu. A. Karpov; Zh. D. Kobalava; V. O. Konstantinov; S. Yu. Martsevich; A. V. Panov; I. V. Sergienko; et al. (Кардиоваскулярная терапия и профилактика)
The high prevalence of persistent dyslipidemia in primary and specialized care patients treated with statins justifies the need to identify its reasons and develop the recommendations on the treatment optimization. At present, Russian studies focusing on the achievement of target lipid levels remain scarce, which emphasizes the importance of the problem and its further investigation. Aim. Cross-sectional epidemiological study which assessed the prevalence of persistent dyslipidemia in statin-treated patients and analysed the predictors of the achievement of target lipid levels. Material and methods. The lipid profile parameters were analysed in 1586 statin-treated out-patients with varied levels of cardiovascular risk, taking into account the type of lipid-lowering therapy and its doses. The assessment of the cardiovascular event (CVE) risk and the definition of target levels of low-density lipoprotein cholesterol (LDL–CH), as well as normal levels of triglycerides (TG) and high-density lipoprotein cholesterol (HDL–CH), was based on the clinical recommendations by the European Society of Cardiology (ESC 2007) and by the European Society of Cardiology and the European Atherosclerosis Society (ESC/EAS 2011). Results. The analysis based on the ESC 2007 recommendations has demonstrated that the target levels of LDL–CH (<2,5 mmol/l for high-risk patients) were not achieved in 53,5% of the participants. The elevation of LDL–CH levels could be isolated or combined with the HDL–CH decrease and/or the TG increase. Low levels of HDL–CH were observed in 32,3% of the patients, while high TG levels were registered in 55,6% of the participants. The achievement of target LDL–CH levels was predicted by the higher-dose statin therapy (odds ratio 0,44). The analysis based on the ESC/EAS 2011 recommendations has shown that the prevalence of target LDL–CH levels was 12,2% in very high-risk patients (<1,8 mmol/l), 30,3% in high-risk patients (<2,5 mmol/l), and 53,4% in moderate-risk patients (<3,0 mol/l). Conclusion. Over a half of the statin-treated patients failed to achieve target levels of LDL–CH. The lowest prevalence of target LDL–CH levels was observed in very high-risk and high-risk patients. The predictors of target LDL–CH level achievement included moderate cardiovascular risk and higher-dose statin therapy. The obtained results suggest that the correction of persistent dyslipidemia in statin-treated patients could be achieved via increasing the satin dose and combining lipid-lowering medications.